(untitled) (Journal of the College of Basic Education, 2022)
Archeology, like all other sciences, witnessed a rapid development in recent times. Many machines and technologies were introduced to this science that contributed to the advancement of this science and its achievement of good results. A new branch of archeology has emerged, the underwater archaeological excavation, which is concerned with the recovery of antiquities and finds from sunken archaeological sites. Italy was the pioneer in this field. And this science has become a reality as part of general archeology, whether in Italy or other countries, where in recent years this science has achieved a prominent position, proving its usefulness and usefulness, not only because it is a tool that provides us with information, but it is an effective and effective incentive in evaluating Results.